Rehabilitation of building affected by the Ecuador s earthquake of 16 april 2016 in the ULEAM (Gaceta Técnica, 2016)
After the earthquake of April 16, 2016 in Ecuador, the first building to be rehabilitated was the Faculty of Computer Science Campus of the University Laica Eloy Alfaro of Manabi (ULEAM), which had moderate damage in the walls due They were not straight and severedamage to the walls of the tier. For Reconstruction these walls were replaced that were made of block or brick with plaster walls flexible and lightweight. In this article it is presented the good behavior plaster walls had in contrast to the brick or block walls, detailing also, some constructive aspects on the correct way of installing. Finally, UN Spectral analysis of the structure was performed using the spectrum of the earthquake of April 16, 2016, magnitude 7.8, obtained in Manta. In the studied structure, lateral displacements and floors drifts were found. To associate with the latter value with the nonexistence of structural damage and solomoderate damage in the masonry of the classrooms and offices and Severe in the stands. Subsequently a new seismic analysis was made considering weight reduction by changing the material of the walls, determining the best seismic behavior UN.
Keywords: earthquake of April 16 2016; Gypsum walls; Faculty of Informatics ULEAM; Ecuador